2007
DOI: 10.1021/np078006q
|View full text |Cite
|
Sign up to set email alerts
|

Kadsuphilols A−H, Oxygenated Lignans from Kadsura philippinensis

Abstract: Eight new oxygenated lignans, kadsuphilols A-H (1-8), were isolated from the leaves and stems of Kadsura philippinensis. Four of the isolated lignans (1-4) possess the normal C18-dibenzocyclooctadiene skeleton, while the other four lignans (5-8) are C19-homolignans possessing a substituted cyclohexadienone ring with a spiro-benzofuranoid moiety. The structures of the isolated metabolites were elucidated through spectroscopic analyses, including 2D NMR experiments. Compounds 1 and 4 are the first report of an R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…The lignans from this family are commonly classified into five classes, i.e., dibenzocyclooctadiene, spirobenzofuranoid dibenzocyclooctadiene, 1,4-diarylbutane, 4-aryltetralin, and diaryltetrahydrofuran [1]. Recent pharmacological studies have revealed that these compounds accounted for anti-oxidant [2,3], anti-HIV [4,5], antihepatitis B virus [6], and anti-proliferative multiple bio-effects [7]. In addition, schisantherin A (2) has been reported to exhibit anti-inflammatory properties by down-regulating NF-kappaB and MAPK signaling pathways in lipopolysaccharide-treated RAW 264.7 cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…The lignans from this family are commonly classified into five classes, i.e., dibenzocyclooctadiene, spirobenzofuranoid dibenzocyclooctadiene, 1,4-diarylbutane, 4-aryltetralin, and diaryltetrahydrofuran [1]. Recent pharmacological studies have revealed that these compounds accounted for anti-oxidant [2,3], anti-HIV [4,5], antihepatitis B virus [6], and anti-proliferative multiple bio-effects [7]. In addition, schisantherin A (2) has been reported to exhibit anti-inflammatory properties by down-regulating NF-kappaB and MAPK signaling pathways in lipopolysaccharide-treated RAW 264.7 cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…Medium ring‐fused benzocarbocycles are important structural motifs that are ubiquitously distributed in a wide range of natural products, bioactive molecules, and even chiral ligands, such as sinensigenin C, heteroclitin I, (−)‐α‐viniferin, and cyclotriveratrylene (Figure ). Despite their importance, the creation of these appealing frameworks still remains a long‐standing challenge in the synthetic community .…”
Section: Figurementioning
confidence: 99%
“…This reaction provides as traightforward, transition-metal-free avenue to preparem edium ring-fused benzocarbocycles by creating "noble"s even-, eight-, and nine-membered rings. Applications of this method in the creation of medium-sized exocyclic and inner benzocyclic olefins, nine-membered lactones,a nd lactams are described.Mediumr ing-fused benzocarbocycles are important structural motifs that are ubiquitously distributed in aw ide range of natural products, bioactive molecules, and even chiral ligands, such as sinensigenin C, [1] heteroclitin I, [2] (À)-a-viniferin, [3] and cyclotriveratrylene [4] (Figure 1). Despite their importance,t he Supportinginformation for this article can be found under http:// dx.…”
mentioning
confidence: 99%
“…1 However, oxa-Michael addition to quinone is underestimated and just stimulates few studies, 2 in spite of its potential in the total synthesis of the related natural products including kadsuphilol H, 3 gephyromycin, 4 and isopinnatal. 5 (see Fig.…”
Section: Introductionmentioning
confidence: 99%